Avaliação pedagógica e de aprendizagem do programa de formação gestão em saúde ofertado pela UNA-SUS/UFMA - SOARES, Maykon Douglas Silva (2022)
Distance Education (EAD) is an education modality that makes it possible to effectively serve large numbers of students, without the risk of reducing the quality of services offered as a result of the increase in the number of students served. The Open University of the Unified Health System (UNA-SUS) was created with the objective of meeting the need for permanent qualifications of workers in the Unified Health System (SUS) who are far from large training centers. It has a network of participating institutions, in which the Federal University of Maranhão is inserted. The objective of this research was to evaluate the reaction in relation to the technical-pedagogical aspects and the learning of the graduates of the Health Management Program (PGS) offered by UNASUS/UFMA. This is an evaluative research with a quantitative approach, based on the theoretical framework of the Kirkpatrick model. The study population consisted of students who completed the PGS, 729. For data collection, three structured instruments were used. After data collection, a descriptive analysis was performed, considering the first two levels of KirkPatrick's evaluation model. The Mann-Whitney test was applied to analyze the significance of pre- and post-course tests. All analyzes were performed using the STATA Program version 14.0. The graduates were 71.57% female, 77.88% higher education, 56.18% SUS workers. The level 1 analysis considered the grades given by the student in the evaluation of the component courses (80% for maximum grade), content evaluation (60% for maximum grade), relevance and achievement of educational objectives (70% for maximum grade) . Level 2 analysis used pre- and post-test scores and self-assessment assignments. There was a statistically significant shift (p<000.1). Evaluation of distance learning activities in Brazil is a growing area gaining relevance as distance courses are developed on a large scale, demanding financial resources for their realization and also a proposal for an evaluative approach. It is believed that this work will contribute to the development of other research in distance education, using evaluative measures following the KirkPatric model.